BIOAVAILABILITAS DAN BIOAKUMULASI LOGAM Pb DAN Cu PADA CABAI RAWIT (Capsicum annuum L.) DI SUBAK SEMBUNG DENPASAR - Bawa, I G. A. G.; Pebriani, N. P. D.; Sudiarta, I W. (Jurnal Kimia (Journal of Chemistry), 2022)
The use of inorganic fertilizers and pesticides can trigger the presence of heavy metals that can pollute agricultural land. The purpose of this study was to determine the bioavailability of Pb and Cu metals in cayenne pepper farms in the Subak Sembung plantation in Denpasar as well as the bioaccumulation of Pb and Cu metals in each part of the cayenne pepper plant. The method used to determine the fractions and bioavailability of Pb and Cu was a squential extraction method, while the bioaccumulation was by the destruction method quantified using the Atomic Absorption Spectrometry (AAS). The results showed that the agricultural land in Subak Sembung Denpasar both before planting and at harvesting contained Pb and Cu metals of 103.2-188.4 mg/kg and 38.3-59.3 mg/kg, respectively. The bioavailability of Pb and Cu in soil was dominated by potentially bioavailable metals (49.67-88.56% for Pb and 51.49-64.18% for Cu), then non-bioavailable (8.40-18.67% for Pb and 33.65-46.94% for Cu) and the smallest was bioavailable (1.95-12.40% for Pb and 0.41-3.31% for Cu). Metal content distributed to each part of the plants, such as Pb in the roots, stems and fruits ranged from 3.05-12.61%, 15.41-16.49%, 41.73-47.91% and 30.26-35.25%, respectively, and for Cu ranged from 42.87-47.91%, 19.13-33.76%, 17.98-26.12%, 4.54-6.84%, respectively. The edible part of cayenne pepper is classified as contaminated with Pb because it exceeds the value set by the Food and Drug Supervisory Agency, which is 0.2 mg/kg. Keywords : Bioavailability, Cu, Pb, cayenne pepper.